2208. Fibrosis Surveillance by Transient Elastography in Patients with Untreated Hepatitis C Infection. (26th November 2018) - Adeyemi, Oluwatoyin; Burke, Kerianne; Winston, Crystal; Markham, Sara; Taussig, Dan; Go, Benjamin; Huhn, Greg
Abstract: Background: Despite the widespread availability of curative HCV therapy and recommendations to consider all HCV-infected patients for treatment, many remain untreated. Illinois medicaid continues to restrict HCV therapy to patients with stage F3 or F4 fibrosis. In our Hepatitis Clinic, untreated patients are counseled and scheduled for follow-up scans at 6–12 months. This keeps patients engaged in care and allows us to identify progression of liver disease. Our study aims were to describe fibrosis assessments in HCV patients and identify predictors of fibrosis progression among untreated HCV-infected patients. Methods: HCV-infected untreated patients with >1 transient elastography by Fibroscan ® between April 2014 and March 2018 and with a baseline scan ≤Stage 2 fibrosis were included in the study. All scans were done by certified operators; 793 (63%) done by one operator. Fibroscan criteria; Stages 0–1 fibrosis; <7.0 kPa and Stage 2 fibrosis; 7.1–9.4 kPa. Results: A total of 545 patients had a total of 1, 260 scans. Median age of 59 years, 64% male, 70% African American, 23% White and 14% Hispanic. 196 (36%) HIV+. 399 (73%) patients had two scans, 127 (23%) patients had three scans and 14 (4%) patients had ≥4 scans. Median time between scans was 12.8 months (range 9.2–17.3 months) with a median duration of 12.8, 24.5 and 40 months between the baseline and second, third or fourth scans respectively. Median baseline score was 6.4 (range 5.3–7.7); 65.3% F0–F1 and 34.7% F2. At last scan, 62% remained at the same stage, 23% had moved 1 stage and 15% regressed from Stage 2 to Stage 1. In the subset who regressed, scores went from 7.8 to 6.1. Conclusion: For the majority of HCV+ patients with mild liver fibrosis at baseline, fibrosis severity remained essentially flat. Progression to moderate/severe fibrosis occurred more often among patients with Stage 2 fibrosis at baseline. Engagement in care remains important to identify patients with fibrosis progression as advocacy to ensure access to curative treatment for all continues. Disclosures: G. Huhn, Gilead: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; ViiV Healthcare: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Janssen: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Theratechnologies: Scientific Advisor, Consulting fee; Proteus: Grant Investigator, Grant recipient.